Acute and Subacute Toxicity Study of Abhraka Bhasma- Incinerated Mica Ash (AYUSHDHARA, 2022)
Among the various Ras dravyas (mineral drugs), Abhraka Bhasma (incinerated mica ash) is widely used in therapeutics. Many herbal and other organic materials have been quoted in reference for various procedures in preparing Abhraka bhasma. It is wonderful that different pharmacological action has been attributed to different Dravyas used in the pharmaceutical processing of Abhraka Bhasma. However, to establish the safety of such metallic and mineral formulation it is the need of the hour to generate scientific data for such drugs. In the present study two samples of Abhraka Bhasma were prepared using two different methods. The safety profile of Abhraka Bhasma samples (AB-1 & AB-2) were evaluated by conducting acute and subacute toxicity study as per OECD Guidelines. Both acute and sub-acute toxicity study demonstrated safety of AB-1 and AB-2 when administered at therapeutic dose, TED X5 dose and TED X10 dose. Even though the sample AB-1 was prepared using a smaller number of Puta, it was sufficient for preparing good quality of Bhasma and was non-toxic